Orange-fleshed Sweetpotato on the home grownschool feeding menu in Nigeria - Phorbee, O.; Ayoola, B.; Njoku, J.; Adesanmi, A. (International Potato Center, 2015)
Sweetpotato for health and wealth in Nigeria and Jumpstarting OFSP in West Africa for diversified markets are two projects that focus on development of the value chain for health and wealth of the rural households in Nigeria, working in Osun and Kwara states. Out of search for OFSP demand at the formal sector, inclusion in the school feeding menu was conceived. The flyer presents the stages of inception, advocacy and sensitization that resulted in the inclusion of OFSP in the School Feeding Program in Osun State, as well as the achievements made between June 2014 and July 2015, and plans for scaling up.